Investors' Portfolio Choice and Tax Reforms: The 2008 German Corporate Tax Reform Reconsidered - Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper provides a comprehensive assessment of the latest German corporate income and capital tax reform, which entails a major shift of the capital tax burden from the firm to the household level. Using a dynamic two-country computable general equilibrium model with integrated capital markets, we show that economic growth and domestic welfare are negatively affected by the reform. Key to the limited growth is the domestic investors' portfolio choice as a channel for tax avoidance at the household (i.e. investor) level. While international investors may well counteract the negative impact on growth, their privileged tax treatment erodes the domestic capital income tax base and thus creates adverse welfare effects.
Keywords: H25; G11; F21; D58; 330; portfolio investment; corporate tax reform; foreign firm ownership; computable general equilibrium